2019
DOI: 10.1002/ca.23488
|View full text |Cite
|
Sign up to set email alerts
|

Age related changes seen in human cornea in formalin fixed sections and on biomicroscopy in living subjects: A comparison

Abstract: The purpose of our experimental research was to assess the effects of aging on the main corneal structures in healthy corneas. Small, human cornea samples were collected from 20 Caucasian subjects during surgery for traumatic lesions to the eye. Ten subjects were adults (mean age 28 years) and 10 were elderly (mean age 76 years). Morphological analysis was carried out using light microscopy and electron microscopy. Another 40 patients (20 young: mean age <30 years; 20 elderly: mean age >70 years) were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…Our results in E. minor indicate that in both the superficial epithelium and the endothelium there is a significant reduction in cell density with age. For the epithelium, our findings are consistent with those of Taurone et al (2020), who found a gradual loss of epithelial cells in humans with an increase in cell size. Similarly, Lemp et al (1990) and Gambato et al (2015) found that the mean diameter of superficial cells of the human cornea increases with age, resulting in a decrease in cell density.…”
Section: Discussionsupporting
confidence: 93%
“…Our results in E. minor indicate that in both the superficial epithelium and the endothelium there is a significant reduction in cell density with age. For the epithelium, our findings are consistent with those of Taurone et al (2020), who found a gradual loss of epithelial cells in humans with an increase in cell size. Similarly, Lemp et al (1990) and Gambato et al (2015) found that the mean diameter of superficial cells of the human cornea increases with age, resulting in a decrease in cell density.…”
Section: Discussionsupporting
confidence: 93%
“…Increased risk of flap dislocation in older patients may be due to age-related changes in the cornea. Senescent changes of the cornea include a reduction in keratocyte and endothelial cell densities [ 18 , 19 , 20 ], corneal stiffening [ 21 , 22 ], epithelial barrier dysfunction [ 23 , 24 , 25 , 26 ], and a greater incidence of dry eye [ 27 , 28 , 29 , 30 ]. We postulate that these and other age-related changes may lead to slower corneal healing and decreased flap adhesion, resulting in a greater incidence of flap dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Keratocytes play a crucial role in corneal wound healing by secreting growth factors and producing collagen [ 32 , 33 , 34 , 35 ]. The reduction in keratocyte density seen with aging likely contributes to slower flap healing in older patients [ 18 , 19 , 20 ]. Theories for the mechanism of early flap adhesion include osmotic pressure due to endothelial pump activity [ 36 , 37 ], electrostatic interactions in the stroma [ 38 ], and epithelial bridging at the edge of the flap [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of inflammatory processes affecting the eye and the exposure to various types of radiations or chemical agents can be directly responsible for the high increase in hydrogen peroxide in the eye, with a consequent increase in ROS responsible for oxidative action. The oxidative action exerted by free radicals at ocular level manifests as structural and functional alterations in the corneal epithelium associated with apoptotic processes in which keratocytes and stromal fibroblasts play a central role (Ung et al, 2017[ 59 ]; Taurone et al, 2020[ 54 ]). In the light of such scientific evidence, the aim of this review was to evaluate the antioxidant effects of ALA and SOD in the visual system, and the possible induction capacity of tissue regeneration following neurodegenerative damage caused by the accumulation of free radicals.…”
Section: Oxidative Stress and The Visual Systemmentioning
confidence: 99%